ANALISIS KOMPONEN HARMONIK PENGAMATAN PASANG SURUT MENGGUNAKAN ALAT PENGAMAT PASANG SURUT BERBASIS SENSOR ULTRASONIK (Studi Kasus: Desa Ujung Alang, Kampung Laut, Cilacap) - Yuwono, Yuwono; Kurniawan, Dedy; Faisal, Nazib (GEOID, 2016)
Tide observations done using two method, simple ways and automatics ways using sensors [4]. Currently in Indonesia there is agency that provider tidal observations data automatically, the Geospatial Information Agency which has 128 observation stations (Geospatial Information Agency, 2016). But the observation stations are only located in major ports and several beaches in Indonesia. While 2/3 of Indonesia is waters that would require mapping bathymetry and tide observations when it will construction, so required for alternative instrumens of automated tidal observers that more flexible and inexpensive. This study aims to determine the analysis of the harmonic components generated by the automatic tide observations using ultrasonic sensors.Tide observations made during the 15 days. The locations were situated in the waters of Ujung Alang, which is part of Segara Anakan river located in Cilacap, Central Java.The Observations data are used to define mean sea level and 9 harmonic components (K1, O1, P1, M2, S2, N2, K2, M4 and MS4). The calculation of Fomzahl value produce type of tides in mix semidiulnal with F= 0,557.